Uganda’s yellow star to launch nutritious bean-based flour to tackle malnutrition - Munthali, Justice; Birachi, Eliud; Rubyogo, Jean Claude (2025)
Malnutrition remains a critical issue in Uganda, with high rates of child stunting and food insecurity. Despite the country’s agricultural resources, nearly one-third of children under five suffer from stunting, and a significant proportion face acute malnutrition. In response, Yellow Star Produce and Food Processors, in collaboration with the Pan-Africa Bean Research Alliance (PABRA), has developed an innovative solution: the Bean-Based Bio-Available Composite Flour. This nutrient-rich flour targets vulnerable populations, including children, expectant mothers, and individuals with chronic illnesses, providing essential nutrients to combat malnutrition. The flour is rich in protein, iron, and energy, supporting growth, immunity, and overall health. By incorporating biofortified beans, pumpkin flour, orange-fleshed sweet potatoes, and millet, Yellow Star ensures enhanced digestibility and nutrient absorption. With a commitment to sustainability and local farmer partnerships, Yellow Star not only offers a healthier alternative to combat malnutrition but also fosters economic and environmental sustainability. This product represents a critical step toward improving food security in Uganda, promoting long-term health and well-being.